A Phase II clinical trial of a mixture of plasma‐derived factor VIIa and factor X (MC710) in haemophilia patients with inhibitors: haemostatic efficacy, safety and pharmacokinetics/pharmacodynamics. (6th June 2013) - Shirahata, A.; Fukutake, K.; Takamatsu, J.; Shima, M.; Hanabusa, H.; Mugishima, H.; Amano, K.; Takedani, H.; Tamashima, S.; Matsushita, T.; Tawa, A.; Tanaka, I.; et al.
Summary: MC710, a mixture of plasma‐derived activated factor VII and factor X at a protein weight ratio of 1:10, is a novel bypassing agent for haemostasis in haemophilia patients with inhibitors. In a Phase II trial, we evaluated the haemostatic efficacy and safety of single doses of MC710, and investigated pharmacokinetic and pharmacodynamic parameters in nine joint bleeding episodes in six male haemophilia patients with inhibitors. This trial was a multi‐centre, open‐label, non‐randomized study of two doses (60 and 120 μg kg −1 as FVIIa dose), allowing the re‐administration of different MC710 dosages to the same subjects. Haemostatic efficacy was assessed by evaluating reduction in pain and swelling, as well as increase in range of motion in a bleeding joint. The results of the study showed that in nine bleeding episodes, seven treatments were rated as 'excellent' or 'effective' according to investigator's rating system of efficacy at 8 h after administration. No serious or severe adverse events were observed after administration; furthermore, measurement of several diagnostic markers revealed no signs or symptoms of disseminated intravascular coagulation (DIC). The haemostatic potential of MC710 was confirmed at doses of 60 and 120 μg kg −1 in this trial. MC710 is thus expected to be a safe and efficacious novel bypassing agent for controlling bleeding in haemophilia patients with inhibitors.